Composite solar façades and wind generators with tensegrity architecture. (15th April 2017) - Cimmino, M.C.; Miranda, R.; Sicignano, E.; Ferreira, A.J.M.; Skelton, R.E.; Fraternali, F.
Abstract: The urgent need for sustainable buildings calls for the adoption of active building façades that harvest wind and solar energy through on-site wind power generators and solar panels. Particularly interesting is the use of tensegrity structures for the construction of renewable energy supplies, due to their easy integration with solar and acoustical panels, which can form special rigid members of the structure. The present study deals with the design of active façades based on tensegrity units, which supports shading devices and/or solar panels. The tensegrity units are foldable and deployable and are controlled by stretching or relaxing selected cables. Wind generators to convert the strain energy stored in the cables of wind-excited units into electrical power are also designed. The proposed structures offer portable applications for small spans and are easy to assemble using prefabricated component parts in the case of large spans.